JENIS DAN KEPADATAN POPULASI SERANGGA PADA PERTANAMAN PADI SAWAH FASE VEGETATIF DI DESA TALAWAAN KECAMATAN TALAWAAN KABUPATEN MINAHASA UTARA - Nintang T. Umboh; Betsy A.N. Pinaria; Jusuf Manueke; Dantje Taroreh (Universitas Sam Ratulangi, 2014)
ABSTRACTThis research aims to know the type and density of the population of insects in paddy rice field in the village of vegetative phase Talawaan Subdistrict of North Minahasa Regency Talawaan. This study used a survey method and direct observation in field. Paddy rice fields used are varieties of musi. Paddy rice acreage is divided into five plot observations that spread diagonally with a size of 3 x 5 meters. The arrest of insect pests is done using the insect nets swung as much as 5 times the double swing at each plot. Insects obtained is then identified by using insect identification key. Things that were observed in this study: Morphology of insects, and insect population count was found. Results of the study showed that there are 8 types of insect pests found i.e. depunctalis, Cnaphalocrosis medinalisNymphula, Scirpophaga (Tryporyza) Leptocorisa oratorius, inotata, Scotinophora coartata, Nephotettix spp., Nilaparvata lugens and Valanga sp. Where the average highest populations of insect pests found in field is Nephotettix spp. i.e. 11,87 tail., L. oratorius 9,33 tail; N. depunctalis and S. innotata 7 tail, 67, N. lugens 4.4 tail, tail 3.27 Valanga spp, C. medinalis 2.93 tail, and on average the lowest population in the meet, the situation is S. coartata which is 2.47 tail.Keywords : Population, insect pests, rice field